2020
DOI: 10.1007/s00428-020-02932-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor-infiltrating T lymphocytes with intestinal-type gastric cancer molecular subtypes and outcome

Abstract: While host immune response is likely to be important for the prognosis of gastric cancer patients, detailed information on the T lymphocyte infiltration in different gastric cancer subtypes is lacking. Here, we studied the presence of CD3, CD8, and FOXP3 (Forkhead box p3) expressing T lymphocytes in a retrospective cohort of 190 intestinal gastric and gastroesophageal adenocarcinomas. The cancers represented four distinct molecular subtypes: Epstein-Barr virus–positive (EBV+), mismatch-repair-deficient (MMR-D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Now, there's no reliable biomarker for distinguishing nTregs from iTregs. In recent years, Foxp3+ T cells have been found in many tumors, such as HCC (17), pancreatic ductal adenocarc (18), colorectal cancer (19), gastric cancer (20), and esophageal cancer (21), suggesting that Foxp3+ T cells participated in the tumor progression. However, the subsets of infiltrating Foxp3+ T cells in tumors remained unclear.…”
Section: Foxp3+ T Lymphocytesmentioning
confidence: 99%
“…Now, there's no reliable biomarker for distinguishing nTregs from iTregs. In recent years, Foxp3+ T cells have been found in many tumors, such as HCC (17), pancreatic ductal adenocarc (18), colorectal cancer (19), gastric cancer (20), and esophageal cancer (21), suggesting that Foxp3+ T cells participated in the tumor progression. However, the subsets of infiltrating Foxp3+ T cells in tumors remained unclear.…”
Section: Foxp3+ T Lymphocytesmentioning
confidence: 99%
“…Indeed, we found a correlation between tumor cell FHOD1 expression and high numbers of CD8 + lymphocytes. TP53-mutated GC tumors generally display lower intratumoral lymphocyte infiltration and wildtype TP53 tumors, in turn, harbor high numbers of infiltrating lymphocytes [24]. We found down-regulation of FHOD1 in TP53 aberrant tumors and upregulation of FHOD1 in tumors with high lymphocyte infiltration.…”
Section: Discussionmentioning
confidence: 54%
“…In our previous study, we stained immune cell markers CD3, CD8 and FOXP3 from the same ngTMA utilized in this study, and saw that high intratumoral infiltration with CD3-and CD8-positive lymphocytes was significantly associated with better outcome [24]. To find out whether there was any association of FHOD1 or FMNL1 expression with intratumoral lymphocyte infiltration in these TMA samples, we tested the correlation between FHOD1 and FMNL1 expression and the number of CD3-, CD8and FOXP3-positive lymphocytes in individual samples.…”
Section: Association Of Fhod1 and Fmnl1 Expression With Intratumoral Lymphocyte Infiltrationmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have found that TDs are present not only in colorectal cancer but also in other solid malignancies, such as gastric, bile duct, and pancreatic cancers [2,16]. Currently, although a few studies have shown that the presence of TDs is an independent prognostic factor for a poor prognosis in gastric cancer [9,10], the mechanism of TDs formation is unclear.For colorectal cancer, the importance of TDs has been recognized and has been included in category N in the 7th edition of the TNM staging system for colorectal cancer. However, in the 8th edition of the TNM staging system, TDs are considered as a metastatic lymph node in gastric cancer, which is contrary to the ndings of the current study.…”
Section: Discussionmentioning
confidence: 99%